2021
DOI: 10.1101/2021.04.07.438755
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cells of the human intestinal tract mapped across space and time

Abstract: The cellular landscape of the human intestinal tract is dynamic throughout life, developing in utero and changing in response to functional requirements and environmental exposures. To comprehensively map cell lineages in the healthy developing, pediatric and adult human gut from ten distinct anatomical regions, as well as draining lymph nodes, we used single-cell RNA-seq and VDJ analysis of roughly one third of a million cells. This reveals the presence of BEST4+ absorptive cells throughout the human intestin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(102 citation statements)
references
References 95 publications
(118 reference statements)
7
95
0
Order By: Relevance
“…An approach in human organoids with an EEC reporter gene yielded sufficient EECs for detailed scRNAseq analysis, though it is unclear how these cells may differ from primary human EECs 132 . While several human scRNAseq studies show EEC data [11][12][13]16,17 , our 154 EECs (Fig. 5G) represent the largest dataset of primary human EECs to our knowledge.…”
Section: Enteroendocrine Cellsmentioning
confidence: 88%
See 3 more Smart Citations
“…An approach in human organoids with an EEC reporter gene yielded sufficient EECs for detailed scRNAseq analysis, though it is unclear how these cells may differ from primary human EECs 132 . While several human scRNAseq studies show EEC data [11][12][13]16,17 , our 154 EECs (Fig. 5G) represent the largest dataset of primary human EECs to our knowledge.…”
Section: Enteroendocrine Cellsmentioning
confidence: 88%
“…FAE includes microfold (M)-cells, which transport luminal antigens to immune cells residing within their microfolds 73 . M-cells have almost exclusively been explored in mice [74][75][76] or using directed differentiation in vitro 77 , with only one study reporting scRNAseq data from healthy human intestinal M-cells 17 . Our dataset includes a cluster of 19 cells from Donor 2 enriched for M-cell markers [78][79][80] and immune cross-talk genes (Fig.…”
Section: Follicle-associated Epitheliummentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding the ISC niche has led to the identification of growth factors that enhance cell type composition and maturation of human small intestinal enteroid cultures (Fujii et al, 2018;Holloway et al, 2021;Jardé et al, 2020). Recent scRNA-seq studies revealed that human small intestinal epithelial development is accompanied by temporal changes of mesenchymal subtype compositions (Elmentaite et al, 2020(Elmentaite et al, , 2021Fawkner-Corbett et al, 2021;Holloway et al, 2021;Yu et al, 2021). ISCs expressing Leucine-Rich Repeat Containing G Protein-Coupled Receptor 5 (LGR5) emerge concomitantly with an increase of subepithelial mesenchymal cells that express a member of the Epidermal growth factor (EGF)-family of secreted ligands, Neuregulin 1 (NRG1), during human intestine development (Yu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%